Effective viscoelastic properties of short-fiber reinforced composites. (March 2016) - Sevostianov, Igor; Levin, Valery; Radi, Enrico
Abstract: The paper focuses on the calculation of the effective viscoelastic properties of a short fiber reinforced composite. The orientation distribution of the fibers is described by a scatter parameter, varying from perfectly aligned fibers to randomly oriented ones. Both matrix and fibers are assumed to be isotropic. The viscoelastic behavior is described using fraction-exponential operators of Scott Blair–Rabotnov. Results are obtained in closed form.